Sintering of FeCuAl powder compacts formed through die compaction process at elevated temperature - Rahman M.M.; Ismail M.A.; Rahman H.Y.; Hasan Z. (Institute of Physics Publishing, 2023)
Aluminum alloys; Argon; Compaction; Copper alloys; Engineering research; Iron alloys; Microstructure; Sintering; Ternary alloys; Constant temperature; Elevated temperature; Experimental investigations; Heating/cooling rate; Sintering characteristics; Uniaxial die compaction; Uniform microstructure; Volumetric expansion; Powders